The proactive leadership at Taif Middle Schools' Leaders in the light of Saudi Vision 2030 from their Perspective - Farag, Shada Ibrahim; Al-Harthy, Iman Abdullah (Journal of Educational and Psychological Sciences, 2022)
The purpose of this study is to measure the proactive leadership of middle schools' leaders at Taif city, Saudi Arabia in the light of Saudi Vision 2030, from their perspective. A descriptive method was used, and a questionnaire was applied to 93 leaders. The results were that Taif's middle schools' leaders have an extremely high level of proactive personality with a total mean (4.50 out of 5). The results showed that they practice the Proactive Leadership skill with a total mean (4.47 out of 5). As for the dimensions; first came Searching For Support with mean (4.55), then Strategic Planning with mean(4.46), and thirdly, Preventive Confrontation with mean (4.40), all of which are at a (very high) degree, With statistically significant differences in the practice of Proactive Leadership skills due to the variables of academic qualification in the dimensions of Strategic Planning and Searching For Support; In favor of holders of bachelor’s qualifications, variable number of years of experience in the dimension of Searching For Support in favor of ten years of experience or more, and variable number of training courses in the dimension of Preventive Coping in favor of ten training courses or more, while there were no statistically significant differences for these variables in the Proactive Personality of the leaders. The study recommended leaders provide their school's work teams the proactive practices, and recommended Administration to give more confidence, authority and empowerment to school leaders and school's work teams in the areas of community partnership and student activities.
Keywords: proactive leadership; Middle school leaders; Saudi Vision 2030